Assessment of PTSD among the Patients Exposed in Highly Stressful Situations Conducted in Shree Birendra Hospital, Chhauni, Kathmandu - Neupane, N K (Medical Journal of Shree Birendra Hospital, 2006)
Assessment of PTSD among the Patients Exposed in Highly Stressful Situations Conducted in Shree Birendra Hospital, Chhauni, Kathmandu